ENT600: McDonald’s Precint 2, Putrajaya franchise / Muhammad Afiq Brohan, Nor Hanani Arifin and Muhammad Zahiruddin Md Din. - Brohan, Muhammad Afiq; Arifin, Nor Hanani; Md Din, Muhammad Zahiruddin (2018)
This study focuses on the management strategy and technology use in a fast-food restaurant which has experienced prosperous growth over the last three decades. McDonalds is a one of a famous and establish fast-food restaurant in Malaysia. To maintain it the company uses advance technology in a number of ways. In fact, without the technology, McDonald's would not be able to operate as it does today. From taking orders to completing the orders everything involves a computer. A network system is used to take the order which is then sent in the back also through the system in order for the food to be cooked.